Malnutrition and Fragility: From Children to Elderly with Probiotics - Salvatella-Flores, Margarita J; Bermúdez-Humarán, Luis G (Archives of Clinical and Biomedical Research, 2020)
The great economic and social disparities, as well as the climatic changes which have caused natural disasters and migration in numerous parts of the planet, have greatly contributed to the increase in malnutrition around the world. Moreover, as if that were not enough, the Declaration of Alma Ata to the Millennium Declaration (in order to reduce poverty and related pathologies such as malnutrition) have not presented satisfactory results yet. Therefore, this review will resume the scientific papers about malnutrition. One of the most serious expression of malnutrition is emaciation or Kwashiorkor, which affects the vulnerability of the individuals from childhood, in most cases, until old age. The keyword global malnutrition, will be linked to the use of probiotics as a preventive way to reduce vulnerability (in children) and frailty (frailty syndrome in the elderly). In this type of patients, there are a susceptibility to other pathologies, especially contracting infections as a result of malnutrition. If an adequate gut microbiota (ecological communities of commensal, symbiotic and pathogenic microorganisms found in the gastrointestinal tract) has been established since childhood, the response to medical treatments and recovery in the elderly stage would probably be better and therefore it would reduce the possible complications and disabling side-effects, of a timely manner. The risk of malnutrition coupled with the frailty syndrome, with a history of a poor microbiota during childhood, can make it difficult for the patient to recover and even lead to death. In contrast, the administration of probiotics can make the intervention timelier and avoid severe complications, even with a fatal outcome.